Politics of Identity in the Indonesian Wayang Comics - Seno Gumira Ajidarma (Mudra Jurnal Seni Budaya, 2017)
As identity become more and more important in the life of a nation-state in the age of globalization, the ideological struggle to be original, like there is an original signifier of â€œIndonesiaâ€, happen as long as the history of wayang comics itself, from 1955 until today. Theoretically come from a Sanskrit source literary epic of Ramayana and Mahabharata, the first evidence of intermediation are the reliefs of Ramayana at Prambanan Temple in the 9th century, as the year 856 AD marked the official use of the temple; and only in the year of 960 an anonymous writer finished the translation of Wirataparwa, part of Mahabharata from Sastra Parwa. Long before come to the comic form, these two epics were the sites of political interest on all of the intermediations, from the Old Javanese translations of the Indianâ€™s Sanskrit, to the shadow play and dance-drama interpretations from the literary sources. The wayang comic itself born as a way out from political repression outside, when in the 1955 comics were hunted to be seized and burn. However, as the wayang comic genre going to be an ideological choice, which the best form, style, and genre to choose is still an ongoing contestation of identity politics to represent Indonesia. Wayang comic is the site of struggle of groups in society with the interest of identity politics with an idea of Indonesia, where the discourse of the sub-ordinated groups appear as a resistance to the discourse of dominant groups.Dengan semakin pentingnya identitas bagi kehidupan negara-bangsa, perjuangan ideologis untuk menjadi asli juga berlangsung sepanjang sejarah komik wayang, dari 1955 sampai hari ini. Terandaikan datang dari sumber susastra epik berbahasa Sanskerta, bukti pertama alihwahananya adalah relief Ramayana di Candi Prambanan pada abad ke-9; dan baru pada 960 terjemahan Wirataparwa, bagian Mahabharata, diselesaikan penulis anonim. Jauh sebelum berbentuk komik, kedua epik ini merupakan situs kepentingan politis segala alihwahana, dari terjemahan Jawa Kuna atas bahasa Sanskerta dari India, sampai kepada penafsiran bagi pementasan wayang kulit dan wayang orang dari sumber-sumber susastra. Komik wayang sendiri lahir sebagai jalan keluar dari tekanan politis, ketika pada 1955 komik dirazia dan dibakar. Betapapun, meski genre komik wayang lantas menjadi pilihan ideologis, bentuk, gaya, dan genre wayang yang mau dipilih masih berada dalam kontestasi politik identitas bagi representasi Indonesia. Komik wayang adalah situs perjuangan dari berbagai kelompok dengan kepentingan politik identitas bagi gagasan Indonesia.